Cannabidiol-Treated Ovariectomized Mice Show Improved Glucose, Energy, and Bone Metabolism With a Bloom in Lactobacillus - Sui, Ke; Tveter, Kevin M.; Bawagan, Fiona G.; Buckendahl, Patricia; Martinez, Savannah A.; Jaffri, Zehra H.; MacDonell, Avery T.; Wu, Yue; Duran, Rocio M.; Shapses, Sue A.; Roopchand, Diana E. (Frontiers in Pharmacology, 2022)
Loss of ovarian 17β-estradiol (E2) in postmenopause is associated with gut dysbiosis, inflammation, and increased risk of cardiometabolic disease and osteoporosis. The risk-benefit profile of hormone replacement therapy (HRT) is not favorable in postmenopausal women therefore better treatment options are needed. Cannabidiol (CBD), a non-psychotropic phytocannabinoid extracted from hemp, has shown pharmacological activities suggesting it has therapeutic value for postmenopause, which can be modeled in ovariectomized (OVX) mice. We evaluated the efficacy of CBD (25 mg/kg) administered perorally to OVX and sham surgery (SS) mice for 18 weeks. Compared to VEH-treated OVX mice, CBD-treated OVX mice had improved oral glucose tolerance, increased energy expenditure, improved whole body areal bone mineral density (aBMD) and bone mineral content (BMC) as well as increased femoral bone volume fraction, trabecular thickness, and volumetric bone mineral density (vBMD). Compared to VEH-treated OVX mice, CBD-treated OVX mice had increased relative abundance of fecal Lactobacillus species and several gene expression changes in the intestine and femur consistent with reduced inflammation and less bone resorption. These data provide preclinical evidence supporting further investigation of CBD as a therapeutic for postmenopause-related disorders.